The Effect of Backpack Carriage in Different Weights and Gradients on Ground Reaction Force Parameters of 10-12 Year Old Schoolchildren's Gait in Tehran, Iran - Fatemeh Ahmadi-Goodini; Mehdi Khaleghi-Tazji; Amir Letafatkar (Vesnu Publications, 2020)
Introduction: Schoolchildren have to carry their backpacks every day on routes with different characteristics and slopes. However, the knowledge available on its effects on walking biomechanics is very limited. Therefore, this study aims to evaluate the effects of backpack carriage in different weights and gradients on the kinetics of schoolchildren's gait.Materials and Methods: 18 primary schoolchildren living in Tehran City, Iran, with age range of 10-12 years completed 7 randomized trials of walking on a treadmill (three tasks on a flat surface, including without a backpack and with backpacks with 10% and 15% of body weight load as the control group, two tasks on a 15% positive gradient, and two tasks on a 15% negative gradient). The values of the vertical ground reaction force parameters including the first force peak, second force peak, mid support force, loading rate, push-off rate, and time-to-peak (TTP) were extracted.Results: The results of analysis of variance (ANOVA) showed that the effect of gradient on the first and second peaks, loading rate, rate of push-off, and TTP of gait was significant (P ≤ 0.001), but the effect of backpack weights on the kinetics was not significantConclusion: Carrying backpacks downhill will has more impacts on the children's motor system, so that it seemed to have a different motor control strategy. The modification of backpack carriage methods can be one of the leading strategies to reduce the negative effects of stress on the musculoskeletal system of children.